RECONSTRUCTION OF URBAN UNDERGROUND LAND ARRANGEMENT FROM THE PERSPECTIVE OF SPATIAL JUSTICE AND REGIONAL AUTONOMY IN SAMARINDA CITY - Khayrul Rizal; Rahmatullah Ayu Hasmiati; Surahman; Aullia Vivi Yulianingrum (PT. Radja Intercontinental Publishing, 2026)
The increasing phenomenon of urban idle land in Samarinda City has become a crucial issue, triggered by the acceleration of urbanization and its strategic role as a buffer zone for the Indonesian Capital City (IKN). The existence of idle land indicates the suboptimal utilization of urban space and gives rise to issues of spatial inequality, land ownership speculation, environmental degradation, and the loss of regional economic potential. On the other hand, the regulation of abandoned land in the national legal system is still centralized under the authority of the Ministry of ATR/BPN, thus unable to accommodate the control of urban idle land by local governments. This study aims to analyze the causes of the inadequacy of the current regulatory design of the Samarinda City Government's authority in regulating idle land in order to realize spatial justice. Furthermore, this study proposes a design for reconstructing local government authority in regulating urban idle land that is in line with the principles of the Rule of Law and the Regional Autonomy framework. This study uses a normative juridical method with a legislative, conceptual, and comparative approach. The results of the study indicate a lack of clarity in the norms of authority between the central and regional governments and the absence of specific regulations regarding idle land in the Samarinda City Regional Regulation on the Spatial Plan (RTRW). To address these issues, it is recommended to establish a Regional Regulation that comprehensively regulates the operational definition of idle land, effective monitoring mechanisms, economic disincentive instruments for owners, and strict administrative sanctions, in order to realize the productive use of urban land and the principle of social justice.